Disruptive Behavior Disorders Symptoms, Evaluation and Treatment - Milone, Annarita; Sesso, Gianluca (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Disruptive behavior disorders (DBD) refer to a group of conditions that typically share difficulties in modulating aggressive conducts, self-control, and impulses, with resulting behaviors that constitute a threat to others' safety and to social norms. Problematic issues with self-control associated with these disorders are commonly first observed in childhood, but may often persist into adolescence and adulthood, or pose a developmental risk for subsequent negative outcomes. The clinical management of DBD in childhood and adolescence has seen great advances in recent years, and research has also focused on identifying early signs, predictors, and risk factors, which may help clinicians to disentangle and subtype the heterogeneous manifestations of BDB. This has allowed significant progress to be made in defining specific developmental trajectories, targeted prevention programs, and timely treatment strategies. The principal aims of this Special Issue were thus to address three core features of DBD clinical management, the multidimensional assessment of callous-unemotional traits, empathic faults and emotional dysregulation, and the available treatment options. In this Special Issue, twelve relevant contributions, including ten original articles, one systematic review, and one study protocol, which provide novel insights for the assessment and treatment of DBD in clinical practice, have been collected by the editors.